Dialectics in Social Thought - Skoll, G. author. aut Link
XIII, 208 p.
Keywords: Dialectics in Social Thought examines the work of thinkers who used dialectics in their attempts to understand the world. Among them are foundational thinkers such as Marx, Freud, and Nietzsche; seminal social critics of the last century such as Camus and Sartre; and current contributors like Badiou, Rancière, and Žižek.